M&A, Competition and Performance in the Slovenian Banking System - Andreea Nicoleta Popovici; Dragos Gabriel Turliuc (CES Working Papers, 2014)
The process of mergers and acquisitions is the main method used by financial institution to grow and to obtain better performance. The main effect of the implication of banks in mergers and acquisitions (M&A) translates into a higher degree of market share of the banks and also that the small banks will soon become global banks. This article underlines the relationship between bank performance and degree of concentration of the Slovenian banking sector during 2006-2012 using a simple linear regression model.
Keywords: F30; G34; L10; 330; banks; M&A; concentration; performance